العلاقات الإيرانية – التركية بعد الحرب الباردة جدلية التعاون – التنافس (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تناولت الدراسة العلاقات الإيرانية – التركية بعد الحرب الباردة حيث ركزت على أهم التجاذبات والتحولات الحاصلة في العلاقات بين الدولتين في ضوء المتغيرات الداخلية والإقليمية والدولية، كما قامت الدراسة بتحليل جدلية التعاون – التنافس التي تحكم مسار العلاقات الإيرانية – التركية منذ نهاية الحرب الباردة؛ فحددت عوامل التعاون بين الدولتين، وعوامل التنافس بينهما في البيئات الثلاثة الداخلية البيئية والإقليمية والدولية.وتوصلت الدراسة إلى أن العلاقات الإيرانية – التركية قد تأثرت بصورة مباشرة بنهاية الحرب الباردة، حيث أدى انهيار الاتحاد السوفييتي إلى تعاظم الدور الإقليمي للدولتين إلى تنامي نفوذهما السياسي في منطقتي الشرق الأوسط وآسيا الوسطى في مسعى منهما للوصول إلى مكانة القوة الإقليمية الكبرى.The study addressed the Iranian – Turkish relations after the cold war and focused on the most important interactions and trans formations takin, place between the two states in light of the international, regional and internal developments.The study also analyzed the dialectic cooperation-competition which takes control of the track of Iranian-Turkish relationship since the end of the cold war as it identified the cooperation and competition factors between the two states in the three environments (internal, regional and international).The study found that the Iranian – Turkish relations have directly been affected by the end of the cold war when the collapse of the Soviet Union led to building up the regional role and political influence of the two states in the Middle East and central Asia in an effort to get the major regional power status in the regional system.The study found that the Iranian – Turkish relations have directly been affected by the end of the cold war when the collapse of the Soviet Union led to building up the regional role and political influence of the two states in the Middle East and central Asia in an effort to get the major regional power status in the regional system.